The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3390/ma4050845
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization and Performance of Templated Silica Membranes in Non-Osmotic Desalination

Abstract: Abstract:In this work we investigate the potential of a polyethylene glycol-polypropylene glycol-polyethylene glycol, tri-block copolymer as a template for a hybrid carbon/silica membrane for use in the non-osmotic desalination of seawater. Silica samples were loaded with varying amounts of tri-block copolymer and calcined in a vacuum to carbonize the template and trap it within the silica matrix. The resultant xerogels were analyzed with FTIR, Thermogravimetric analysis (TGA) and N 2 sorption techniques, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The PWF of geopolymer inorganic membranes. The trends of geopolymer inorganic membranes' PWF (pure water flux) [9], water-glass's modulus and H 2 O/Na 2 O ratio could be judged from Fig. 3, there was a certain regularity: under identical H 2 O/Na 2 O ratio, PWF reduced along with the increase of modulus; Under the same modulus, PWF increased along with the H 2 O/Na 2 O ratio's augment.…”
Section: Resultsmentioning
confidence: 96%
“…The PWF of geopolymer inorganic membranes. The trends of geopolymer inorganic membranes' PWF (pure water flux) [9], water-glass's modulus and H 2 O/Na 2 O ratio could be judged from Fig. 3, there was a certain regularity: under identical H 2 O/Na 2 O ratio, PWF reduced along with the increase of modulus; Under the same modulus, PWF increased along with the H 2 O/Na 2 O ratio's augment.…”
Section: Resultsmentioning
confidence: 96%
“…However, this long term testing successfully demonstrated the improved hydro-stability of CoOxSi membranes at several temperature points and feed concentrations. In the only other studies reported thus far, Duke et al reported stable performance over 5 h of the CTMSS (Ionic 6) membrane [19]; and Ladewig et al showed stable performance over 12 h, suggesting the benefit of the carbonized templating method to improve the hydro-stability of amorphous silica membranes [68]. …”
Section: Membrane Performance: Effect Of Testing Conditionsmentioning
confidence: 99%
“…However, the water vapour pressure change as a function of the salt concentration at constant temperature is not large enough to justify the large reduction of flux as reported by several groups in Table 1. For instance, in the case of carbonized template CTMSS (ionic C6), experiment was conducted at a fixed temperature of 20 °C [68]. Indeed, water flux was reduced by more than half (56%) by increasing the feed concentration from 0.3 wt % to 3.5 wt %.…”
Section: Membrane Performance: Effect Of Testing Conditionsmentioning
confidence: 99%
See 1 more Smart Citation